PENERAPAN SISTEM MANAJEMEN INFORMASI BAZNAS (SIMBA) PADA BADAN AMIL ZAKAT NASIONAL KABUPATEN MAJALENGKA - Yasmin Sherlly Aulia; Gina Sakinah (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze the effectiveness of implementing the BAZNAS Management Information System Application (SIMBA) in reporting the management of zakat, infaq, and sadaqah (ZIS) funds at BAZNAS Majalengka Regency. SIMBA is an official application developed by the National Amil Zakat Agency (BAZNAS) to support transparency, accountability, and standardization in ZIS fund management across Indonesia. This research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation involving BAZNAS Majalengka officials. The findings indicate that the implementation of SIMBA at BAZNAS Majalengka has been effective in improving the quality of ZIS financial reporting. The application facilitates the preparation of reports in accordance with zakat accounting standards, enhances transparency to the public, and accelerates the reporting process to the BAZNAS central office. However, in daily practice, technical challenges are encountered, particularly in the daily closing process, which becomes more complex due to the large number of codes and items that must be entered. With improvements in human resource capacity and technological infrastructure support, SIMBA has the potential to serve as a crucial instrument in strengthening ZIS governance to be more professional and aligned with public accountability principles.